Persepsi Pelaku Usaha Mikro Kecil Menengah terhadap Kewajiban Sertifikasi Produk Halal - Azizah, Isnaenatul; Alkhaezuri, Alwan Isya; Hasanah, Afifa Nur (SIL'AH: Jurnal Ekonomi Syariah, 2024)
This research aims to obtain data related to the perceptions of micro, small and medium enterprises around the UIN K.H. campus. Abdurrahman Wahid Pekalongan regarding the obligation to certify halal products. This type of research is field research with descriptive qualitative methods. The data obtained from this research was through interviews with 10 micro, small and medium enterprises located around the UIN K.H. Abdurrahman Wahid Pekalongan campus. Based on research results, it shows that only 10% of micro, small and medium enterprises already have a halal certificate, 80% of micro, small and medium enterprises already know about the existence of halal certificates, 90% of micro, small and medium enterprises consider that halal certification is important for products, and 40% Micro, small and medium enterprises have never received any socialization regarding halal product certification. Apart from that, there are several factors that influence the perceptions of micro, small and medium enterprises regarding halal product certification.. This research contributes to the importance of the role of authorised institutions to maximise the halal certification program for the development of the halal industry in society.